Respuesta :

Answer:

Step-by-step explanation:

hello :

x²+ y² + 6x - 4y - 27 = 0 means : (x²+6x+9)-9+(y²-4y+4)-4-27 =0

(x+3)²+(y-2)² = 40....standard form when the center is (-3 , 2) and radius √40

The center is (-3, 2), and the radius root40.

We have given

x²+ y² + 6x - 4y - 27 = 0

It can be written as

(x²+6x+9)-9+(y²-4y+4)-4-27 =0

Write the given equation in standard form

What is the standard form of the circle?

(x-a)^2+(y-b)^2=r^2

Where (a,b) be the center and

r-is the radius of the circle

(x+3)²+(y-2)² = 40

Compare the above equation with the standard form of the equation

The center is (-3, 2), and the radius root40.

To learn more about the circle visit:

https://brainly.com/question/24375372

#SPJ2